Efektifitas Pembelajaran Berbasis Critical Thinking Terhadap Pengembangan Nalar Kritis Santri Di Pondok Pesantren An-Nur Banjarejo Kabupaten Blora - Habib Hidayat; A. Zaenurrosyid; Ahmad Muflihin (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
This study aims to analyze the effectiveness of critical thinking-based learning on the development of students’ critical reasoning skills in the learning of Hadith Arbain Nawawi at An Nur Islamic Boarding School, Banjarejo, Blora Regency. The study was motivated by the urgency of strengthening critical thinking skills in Islamic education amid contemporary educational challenges that require analytical, reflective, and argumentative competencies. This research employed a quantitative approach using a posttest-only control group design. The research sample consisted of 46 MTs-level students divided into an experimental class of 26 students and a control class of 20 students. Data collection was conducted through critical reasoning tests in the form of argumentative essays and HOTS-based case studies related to Hadith Arbain Nawawi materials. The data were analyzed using the Shapiro–Wilk normality test, Levene homogeneity test, and independent sample t-test with a significance level of 0.05. The findings revealed that the hypothesis test obtained a significance value of < 0.001 with a t-value of 4.453. These findings indicate a significant difference in critical reasoning skills between the experimental and control classes. This study concludes that critical thinking-based learning is effective in developing students’ analytical, argumentative, and reflective reasoning skills in the learning of Hadith Arbain Nawawi within the Islamic boarding school environment.